2006
DOI: 10.1002/ijc.21937
|View full text |Cite
|
Sign up to set email alerts
|

A microsatellite polymorphism in the heme oxygenase‐1 gene promoter is associated with risk for melanoma

Abstract: Heme oxygenase-1 (HO-1) has been demonstrated to play an important role in the regulation of signaling systems, which are involved in the control of cell cycle progression and apoptosis. Recently, a (GT)n dinucleotide repeat polymorphism in the HO-1 promoter was shown to modulate HO-1 gene expression. Short (<25 GT) repeats are associated with an increased HO-1 upregulation after stimulation than are longer repeats. Malignant melanoma (MM) is the most serious cutaneous malignancy with high tendency to aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
55
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 21 publications
3
55
0
1
Order By: Relevance
“…This may, in part, explain why individuals in the highest tertile of iron consumption carrying two short HO-1 alleles were found to be at nonsignificantly elevated risk of breast cancer compared with LL individuals. In support of this, homozygous carriers of short repeats have been found to be at greater risk of malignant melanoma compared with L and M allele carriers (102).…”
Section: Discussionmentioning
confidence: 83%
“…This may, in part, explain why individuals in the highest tertile of iron consumption carrying two short HO-1 alleles were found to be at nonsignificantly elevated risk of breast cancer compared with LL individuals. In support of this, homozygous carriers of short repeats have been found to be at greater risk of malignant melanoma compared with L and M allele carriers (102).…”
Section: Discussionmentioning
confidence: 83%
“…Analysis of HO-1 promoter polymorphism in healthy people and cancer patients indicates that the risk of acquiring and more serious progression of malignant melanoma is significantly higher in people harboring a shorter (GT)n repeats sequence, associated with a higher HO-1 activity. 65 It must be stressed, however, that effects of HO-1 activation may be different in the case of tumor induction compared with tumor progression. Two clinical trials analyzing the frequency of tumor development (oral squamous cell carcinoma in betel chewers and lung adenocarcinoma in cigarette smokers) have suggested that high expression of HO-1 may be beneficial for patients and may decrease the incidence of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…GT-dinucleotide repeats in the promoters of several genes have been associated with the risk of suffering breast cancer, schizophrenia, melanoma, and atherosclerosis, among other diseases. [27][28][29][30][31] Microsatellite polymorphisms in the promoter of the heme oxygenase-1 and matrix metalloproteinase-9 genes have been associated with angiographic restenosis after coronary stenting and the progression of intima-media thickening and constrictive remodeling of carotid atherosclerotic plaques, respectively. 30,31 (GT)n repeat is one of the most frequent variation in the human genome and, when located in a promoter region, may affect transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%